Potret Tuturan Direktif Kata Pengantar: Portofolio Mata Kuliah Membaca Menulis Bahasa Jawa - Lazuardi Imaniar; Anang Santoso; Teguh Tri Wahyudi (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Directive speech is understood as a speech event (behavior) that aims to create or appear a certain action desired by the speaker to the speech partner. Communication carried out by two parties requires an understanding of the language knowledge of the parties concerned. The purpose of the research is to describe the form, function, and strategy of directive speech contained in the introduction to a portfolio of Javanese reading and writing courses. The method used is descriptive method because it is adjusted to the objectives to be achieved. The literature study technique used by the researcher is done by collecting materials from various written sources, with the library study technique the role of the researcher is very influential with the results presented. The data analysis technique used by the researcher begins with carefully reading all the collected data, then data reduction is carried out, and the data is ready to be presented. The results of the study are indicated by the situation of speech forms which are marked by certain words, speech functions are characterized by the dominance of sentences in the collected data, and speech strategies are indicated by the dominance of understanding the context that is raised by the speaker to his interlocutor. Keywords: foreword, Javanese language portfolio, directive speech Abstrak: Tuturan direktif dipahami sebagai peristiwa (perilaku) bertutur yang bertujuan untuk penciptaan atau pemunculan adanya suatu tindakan tertentu yang dikehendaki oleh penutur kepada mitra tutur. Komunikasi yang dilakukan oleh dua pihak diharuskan ada pemahaman pengetahuan bahasa atas pihak terkait. Tujuan dari penelitian yakni dipaparkannya bentuk, fungsi, dan strategi dari tuturan direktif yang terdapat dalam kata pengantar portofolio mata kuliah membaca menulis bahasa Jawa. Metode yang digunakan adalah metode deskriptif, karena disesuaikan dengan tujuan yang akan dicapai. Teknik studi kepustakaan yang digunakan peneliti dilakukan dengan cara dikumpulkannya bahan dari berbagai sumber tertulis, dengan teknik studi kepustakaan peran yang dimiliki peneliti sangat berpengaruh dengan hasil yang disajikan. Teknik analisis data yang digunakan peneliti diawali dengan dibaca cermat seluruh data terkumpul, kemudian dilakukan reduksi data, dan data siap untuk disajikan. Hasil dari penelitian ditunjukkan dengan situasi bentuk tuturan yang ditandai kata tertentu, fungsi tuturan ditandai dengan dominasi kalimat pada data terkumpul, dan strategi tuturan ditunjukkan dengan dominasi pemahaman konteks yang dimunculkan oleh penutur kepada mitra tuturnya. Kata kunci: kata pengantar, portofolio bahasa Jawa, tuturan direktif